2014
DOI: 10.1373/clinchem.2013.209478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Normalization Strategies Used in Real-time Quantitative PCR Experiments in HepaRG Cell Line Studies

Abstract: BACKGROUND The HepaRG cell line is widely used as an alternative for primary human hepatocytes for numerous applications, including drug screening, and is progressively gaining importance as a human-relevant cell source. Consequently, increasing numbers of experiments are being performed with this cell line, including real-time quantitative PCR (RT-qPCR) experiments for gene expression studies. CONTENT When RT-qPCR experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Of course, the fact that these six can be assessed for the validity of the reference genes used does not automatically mean they contain reliable results. The results of our analyses are similar to those of a recent study looking at normalisation in the context of the HepaRG cell line, which is widely used as an alternative for primary human hepatocytes (Ceelen et al., 2013). The authors of this study concluded that not one of the 24 reviewed studies used a proper normalization method.…”
Section: Discussionsupporting
confidence: 85%
“…Of course, the fact that these six can be assessed for the validity of the reference genes used does not automatically mean they contain reliable results. The results of our analyses are similar to those of a recent study looking at normalisation in the context of the HepaRG cell line, which is widely used as an alternative for primary human hepatocytes (Ceelen et al., 2013). The authors of this study concluded that not one of the 24 reviewed studies used a proper normalization method.…”
Section: Discussionsupporting
confidence: 85%
“…It has been demonstrated that under different experimental conditions and during differentiation, the analysis of HepaRG RT-qPCR data showed a lack of reproducibility and validity as a properly established normalization method had not been applied [13,14]. This was also seen when iPS cells were differentiated to hepatocyte-like cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these guidelines can help researchers with the set-up of qPCR experiments to conform to the posed guidelines and standardize qPCR experimental set-up. Alas, despite a wide acceptance of these guidelines within the specialized field of qPCR, recent literature reviews indicate that these guidelines have not been sufficiently adopted by a larger group of researchers [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%